The role of integrated digital systems (ERP) in enhancing communication between business management and public administrations (Comprehensive Journal of Science, 2025)
This study aimed to analyze the role of the Enterprise Resource Planning (ERP) system in enhancing institutional communication between business management and public departments, focusing on administrative and organizational aspects without delving into technical details. The study adopted a descriptive-analytical approach and included a sample of 100 employees from institutions that actively implement ERP systems, during the period from 2024 to 2025.The results indicated that the ERP system significantly contributes to accelerating administrative task completion, improving the quality of decision-making, reducing repetitive errors, and enhancing the efficiency of planning and administrative coordination. Statistical analyses also revealed variation in the perceived impact of the system among departments, reflecting differences in experience and implementation. The study concluded that ERP is an effective digital tool for supporting institutional performance, provided that appropriate infrastructure, adequate employee training, and functional integration across departments are in place. The study recommended expanding the use of ERP systems, developing them in line with institutional needs, promoting a digital transformation culture, and supporting future research in the field of administrative digital systems.